Nudging and boosting children’s restaurant menus for healthier food choice: a blinded quasi-randomized controlled trial in a real life setting - Schneider, Sven; Markovinovic, Jessica; Mata, Jutta (BMC public health, 2022)
Restaurants are ideal settings for implementing food interventions targeted at children. Studies with adults suggest that changes to the physical menu can lead to healthier food choices; online studies with parents indicate that specific menu designs facilitate healthier choices. However, it is unknown whether applying well-established nudging and boosting methods to children’s menus also increases their choice of healthier meals in a real-world restaurant setting.
Gesehen am 22.06.2023